О природе кальцийсодержащего уранинита - Вальтер, А.А.; Писанский, А.И. (Видавничий дім "Академперіодика" НАН України, 2008)
The investigation of calcium-bearing uraninite from ores of the Severinskoe deposit of albitite-uranium formation of the central part of the Ukrainian shield is performed. On the electron microscopy level of investigation, the mineral is homogeneous and has the stoichiometric atomic ratio, Ca : U = 1 : 2. The powder diffraction pattern is the same as that for uraninite with a0 = 0.537(±0.001) nm. The identity of the mineral with artificial compound CaU2O6 with the fluorite-type structure is assumed.